Blueprint for Transparency at the U.S. Food and Drug Administration: Recommendations to Advance the Development of Safe and Effective Medical Products. Issue 4 (2017) - Sharfstein, Joshua M.; Miller, James Dabney; Davis, Anna L.; Ross, Joseph S.; McCarthy, Margaret E.; Smith, Brian; Chaudhry, Anam; Alexander, G. Caleb; Kesselheim, Aaron S.
Abstract : Background: The U.S. Food and Drug Administration (FDA) traditionally has kept confidential significant amounts of information relevant to the approval or non-approval of specific drugs, devices, and biologics and about the regulatory status of such medical products in FDA's pipeline. Objective: To develop practical recommendations for FDA to improve its transparency to the public that FDA could implement by rulemaking or other regulatory processes without further congressional authorization. These recommendations would build on the work of FDA's Transparency Task Force in 2010. Methods: In 2016-2017, we convened a team of academic faculty from Harvard Medical School, Brigham and Women's Hospital, Yale Medical School, Yale Law School, and Johns Hopkins Bloomberg School of Public Health to develop recommendations through an iterative process of reviewing FDA's practices, considering the legal and policy constraints on FDA in expanding transparency, and obtaining insights from independent observers of FDA. Results: The team developed 18 specific recommendations for improving FDA's transparency to the public. FDA could adopt all these recommendations without further congressional action. Funding: The development of the Blueprint for Transparency at the U.S. Food and Drug Administration was funded by the Laura and John Arnold Foundation.